2022
DOI: 10.1111/gcb.16099
|View full text |Cite
|
Sign up to set email alerts
|

Diverging patterns at the forest edge: Soil respiration dynamics of fragmented forests in urban and rural areas

Abstract: As urbanization and forest fragmentation increase around the globe, it is critical to understand how rates of respiration and carbon losses from soil carbon pools are affected by these processes. This study characterizes soils in fragmented forests along an urban to rural gradient, evaluating the sensitivity of soil respiration to changes in soil temperature and moisture near the forest edge. While previous studies found elevated rates of soil respiration at temperate forest edges in rural areas compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 109 publications
(192 reference statements)
3
37
0
Order By: Relevance
“…Soil N cycling rates are well known to be associated positively with soil properties such as moisture (Guntiñas et al, 2012), pH (Cheng et al, 2013), and organic matter content (Cookson et al, 2007), but negatively associated with soil bulk density (Tan & Chang, 2007) and electrical conductivity (Green & Cresser, 2008). Among these factors, soil moisture has been shown to be lower in urban forests and at forest edges, including at the forested sites in this study (Garvey et al, 2022), but the combined effects of all these soil properties on soil N cycling are not well quantified in urban and fragmented temperate forests.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Soil N cycling rates are well known to be associated positively with soil properties such as moisture (Guntiñas et al, 2012), pH (Cheng et al, 2013), and organic matter content (Cookson et al, 2007), but negatively associated with soil bulk density (Tan & Chang, 2007) and electrical conductivity (Green & Cresser, 2008). Among these factors, soil moisture has been shown to be lower in urban forests and at forest edges, including at the forested sites in this study (Garvey et al, 2022), but the combined effects of all these soil properties on soil N cycling are not well quantified in urban and fragmented temperate forests.…”
Section: Introductionmentioning
confidence: 64%
“…This lack of consistency in the literature regarding which aspects of urbanization most strongly affect nutrient cycles is likely due to the heterogeneity of urban environments. Garvey et al (2022), for example, found variation in soil respiration at the same eight study sites was more strongly related to %ISA than to distance to Boston. As such, we conclude that it is important to consider multiple metrics of urbanization, and how they interact with each other, when assessing the impacts of cities on nearby forests.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations